2017
DOI: 10.1002/sia.6342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clay and surface plasma‐treated carbon fiber on wear behavior of thermoplastic POM composites

Abstract: In engineering applications, experimental data and insight from scientific investigations on wear properties of polyoxymethylene (POM) composites are important for engineers to understand how to design and formulate POM materials with high resistance to wear. In this work, clay and carbon fiber were utilized and incorporated into POM and the mechanical and wear properties, in specific wear rate, were then assessed. The experimental results suggested that the addition of clay increased the tensile modulus and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The addition of clay improves the mechanical strength of the CF/POM composite. The fillers' synergistic effect on improving Friction, wear behavior, and morphology was reported [5][6] [8,11] ( Mittal et al 2015) have systematically investigated the importance of surface treatment of MMT clay and its influence on the interaction with reinforced materials, resulting in better adhesion, which consequently influences friction and wear behavior of polymer composite. They found a decrease in the value of the frictional coefficient concerning the sliding time with the decrease in frequency level, keeping the normal load constant within the observed range.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of clay improves the mechanical strength of the CF/POM composite. The fillers' synergistic effect on improving Friction, wear behavior, and morphology was reported [5][6] [8,11] ( Mittal et al 2015) have systematically investigated the importance of surface treatment of MMT clay and its influence on the interaction with reinforced materials, resulting in better adhesion, which consequently influences friction and wear behavior of polymer composite. They found a decrease in the value of the frictional coefficient concerning the sliding time with the decrease in frequency level, keeping the normal load constant within the observed range.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to modify the mechanical and tribological properties of POM. Some researches have been presented to improve the mechanical and tribological properties of POM using fillers, such as PTFE, graphite, and CF 12–17 . However, the addition of different fillers cannot always improve the mechanical and tribological properties of the POM matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 14 investigated the addition of 10%–20% PTFE to POM and found that the tribological properties, toughness, and creep resistance of the composites were significantly improved. Niu et al 15 used clay and carbon fibers and added them to POM and then evaluated their mechanical properties and wear properties. Liu et al 16 investigated the tribological behavior of Si3N4‐based ceramics on POM under distilled water, seawater, and dry sliding conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation